Pengaruh Massa Dan Waktu Kontak Terhadap Penyisihan Zat Warna Air Gambut Menggunakan Adsorben Sekam Padi - Putri Ayu Puspita; Syarfi Daud; Edward Edward (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Peat water is surface water that is blackish brown in color which requires effective and efficient processing to be suitable for use by the community. Various types of adsorbents continue to be developed, one of which is the adsorption of rice husk. The purpose of this study was to determine the removal of dyes in peat water, calculate the adsorption capacity and compare the results of the analysis with the quality standards of the Republic of Indonesia Ministry of Health No. 416 / MENKES / PER / IX / 1990. The fixed variable used in this study is stirring speed 100 rpm and particle size +170 mesh. The independent variables used consisted of variations in the mass of the adsorbent 1.5; 2; 2.5; 3 gr and stirring time 30, 60, 90 and 120 minutes. Dyestuff removal efficiency 57.16% at 3 gr adsorbent mass with 60 minutes contact time. The highest capacity for adsorption of dyestuff was achieved at a mass of 1.5 g with a contact time of 60 minutes of 94.12 mg / gr. The results of the study are not in accordance with the Minister of Health Regulation No.416 / MENKES / PER / IX / 1990, the results obtained exceed the quality standard of 687 PtCo. Keywords: Adsorption, Adsorbent, Peat Water, Rice Husk.